(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The court of initiation, in general, is the holder of the general qualitative and value competence, whether in civil or commercial matters, but as a result of the expansion of the state’s intervention in most areas, economic openness and activity in the commercial market movement and foreign investment, and for the issuance of the Iraqi Investment Law No. (13) of 2006 and the private investment law in Oil Liquidation No. (64) for the year 2007 and for the purpose of encouraging attracting foreign investors to work in Iraq within a workable environment in which the foreign party is assured of the existence of a specialized judiciary that works on resolving disputes arising from administrative contracts in which a foreign party is involved. All of this led to the creation of a specialized judiciary independent of The civil judiciary has jurisdiction over disputes related to administrative contracts. That is why the Court of First Instance to review commercial cases was formed according to the statement issued by the Supreme Judicial Council No. (36_Q_A) dated 01/11/2010. Among the terms of reference assigned to this court is the specific jurisdiction in examining government contracting lawsuits (the subject of our discussion), as a court of the first instance has been designated to examine the disputes related to contracting contracts called (the court of the first instance competent to examine contracting contract disputes). This court was formed with a statement issued by the Supreme Judicial Council on 01/23/2012, but this court was canceled with a subsequent statement and its competencies were transferred to the court of the first instance competent to hear commercial cases according to the statement issued by the Supreme Judicial Council dated 26/11/2014 and previously referred to. According to the foregoing, the jurisdiction of the Court of First Instance, which is competent to consider commercial cases, is to consider commercial lawsuits in which one of the parties is a foreigner, and lawsuits for government contracting contracts (administrative contracts), and lawsuits for investment contracts, companies, and trademarks. And that our research will be limited to research in the jurisdiction of this court, which is related to looking into disputes related to administrative contracts only.